Effects of Steam Injection Flow in Burner and Outside Water Tube to the Increasing of Boiler Temperature - M. Djoni Bustan (ASEAN Journal of Chemical Engineering, 2007)
Energy is an expensive basic need for human life, especially energy from fossils, such as crude oil, gas, and coal. In an oil refinery factory or electrical generator unit, where heat is most dominantly utilized, the boiler is used to generate steam. The main problem in a boiler is its uncompleted combustion process because of the incomplete ratio of air–fuel. This problem is caused by the addition of deposits or sealing inside and outside of the tube fire heater which will reduce the performance of fired heater. The objective of this research is to study the effect of steam flow variation on burner and tubing for increasing heat and temperature as well as the quality of steam. This research used a package boiler B&W series 1986 model which can be seen at an oil refinery factory or steam power electrical generator unit in Indonesia. This package boiler has 50kg/hours steam production capacity, qualified superheated steam, maximum pressure and temperature at 7kg/cm2 and 700oC. Quantitatively, the achievable heat efficiency which corresponded to the temperature increase caused by the steam injection is 41.25% and the specific enthalpy is 12.07%.